Anorexia nervosa with subsequent onset of schizophrenia: A case report and literature review - Suzuki, Yuhei; Sato, Akiko; Mori, Yuhei; Shishido, Risa; Itagaki, Shuntaro; Miura, Itaru (PCN reports, 2025)
Anorexia nervosa (AN) is closely associated with schizophrenia. A recent meta-analysis reported that the comorbidity of eating and psychotic disorders is approximately 8%, suggesting a potential link between the two. However, the characteristics and management of AN patients who later develop schizophrenia remain insufficiently explored. We report a 17-year-old woman with AN since age 11. Despite multiple hospitalizations and behavioral interventions, she persisted in restrictive eating. Additionally, she exhibited emotional dysregulation, irritability, and self-injurious behavior, which led to low-dose risperidone initiation. At age 16, she developed persecutory delusions and auditory hallucinations, resulting in a diagnosis of schizophrenia. Notably, her disordered eating resolved following the onset of psychotic symptoms. With a higher dose of risperidone, her psychosis improved, and she remained stable without relapse or significant weight loss for over a year. This case illustrates the potential relationship between AN and schizophrenia, suggesting that AN may represent a prodromal phase of schizophrenia. Our literature review indicates that the timing and nature of psychotic symptoms can aid in differentiating psychosis linked to AN from schizophrenia. The case also suggests that AN and schizophrenia may exert mutually inhibitory effects on each other, potentially influencing their respective courses.